2007
DOI: 10.1002/pip.779
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the long time behavior of the metastable boron–oxygen complex in crystalline silicon

Abstract: Boron and oxygen contamination in Czochralski-grown (Cz) silicon leads to a degradation of the minority charge carrier lifetime within short times due to the formation of recombination active complexes. The formation of these complexes is investigated for longer times showing a further development of the defect. This development called 'regeneration' is triggered by illumination or applied forward voltages and leads to a new state of the defect. This new state of the defect is proven to be less recombination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 11 publications
(16 reference statements)
5
83
0
3
Order By: Relevance
“…Herguth et al have shown that active BO related defects can be transformed into a recombination inactive state being stable under solar cell operating conditions by applying a regeneration procedure consisting of a combination of carrier injection and slightly elevated temperatures [10,11]. Recent results suggest that hydrogen might be the key factor to fast regeneration processes [12,13]: It has been shown, that if more hydrogen is introduced into the silicon bulk realized e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Herguth et al have shown that active BO related defects can be transformed into a recombination inactive state being stable under solar cell operating conditions by applying a regeneration procedure consisting of a combination of carrier injection and slightly elevated temperatures [10,11]. Recent results suggest that hydrogen might be the key factor to fast regeneration processes [12,13]: It has been shown, that if more hydrogen is introduced into the silicon bulk realized e.g.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, much effort has been put into mitigating lightinduced degradation. Most solutions rely on avoiding the use of 1-2 X-cm boron-doped Cz silicon, 7 but Herguth et al 8 have developed a technique to actually remove LID from silicon. However, the technique is based on illuminating silicon above 90 C for extended periods.…”
mentioning
confidence: 99%
“…The same effect occurs in boron doped p type [7 9] as well as n type [10,11] silicon partially compensated or overcompensated with phos phorus or co doped with gallium. BO defects can be transformed into a recombination inactive state that is stable under carrier injection by the regeneration reaction that requires a combination of slightly elevated temperatures (typically 60 200°C) and carrier injection [12,13], applied to hydrogenated silicon wafers [14 16]. This reaction may be identified (after the first occurring degra dation reaction) by an asymptotically saturating recovery of the carrier lifetime or an asymptotical decrease of the defect density.…”
Section: Introductionmentioning
confidence: 99%